The CSF Vancomycin Concentration in Patients With Post-operative Intracranial Infection Can Be Predicted by the WBCs to Total Cells Ratio and the Serum Trough Concentration - Fan, Ming-Chao; Sun, Jia-Lin; Sun, Jian; Ma, Jun-Wei; Wang, Nian; Fang, Wei (Frontiers in Neurology, 2022)
Background The pharmacokinetics of vancomycin in cerebrospinal fluid (CSF) is an important basis for evaluating the bactericidal effect. The accuracy of using serum vancomycin concentrations only to estimate the CSF concentrations remains controversial, may lead to underdosing. Objectives The aims of this study were to evaluate the vancomycin exposure in CSF, investigate the factors affecting the vancomycin blood–brain barrier (BBB) penetration, and to establish the prediction model of vancomycin concentration in CSF. Methods Eligible patients were included and given a standard dose of vancomycin. At the fifth dose, the blood and CSF samples were collected 0.5 h before the start of infusion of vancomycin, and 1, 2, 3, and 8 h from the start of infusion, and were measured by the enzyme-multiplied immunoassay technique using the Siemens Viva-E Drug Testing System. Results The AUCCSF/serum of patients with intracranial infection was higher than that of patients without (p = 0.001). The CSF concentration was relatively stable between dosing periods (p = 0.095). The area under the concentration–time curve (AUC) ratio of CSF to serum (AUCCSF/serum) in patients with intracranial infection ranged from 15.1 to 80.1% (33.23 ± 19.31%; median, 26.25%). The CSF vancomycin AUC levels were affected by the serum trough concentration (B: 5.23 ± 2.36, t = 2.22, p = 0.039), and were mainly affected by the CSF white blood cells (WBCs)/total cells (B: 113.96 ± 35.10, t = 3.25, p = 0.004) (Y = −17.86 + 5.23 × serum trough concentration + 113.96 × CSF [WBCs/total cells]; R2 = 0.473, F = 8.542, p = 0.002). Conclusions After intravenous administration of vancomycin, the CSF concentration curve was fluctuated gently. The CSF vancomycin concentration in patients with postoperative intracranial infection can be predicted by the WBCs to total cells ratio and the serum trough concentration, and help to adjust the administration of vancomycin.